PENGARUH DISIPLIN KERJA, LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PDAM TIRTA REMU SORONG PAPUA BARAT - Bambang Sunatar (Jurnal Ilmu Manajemen, 2023)
Conceptually, work discipline and a conducive work environment allow employees to work optimally. This study aims to determine the influence of work discipline and work environment on employee performance at PDAM Tirta Remu Sorong West Papua. Quantitative research with a population of 65 employees is used. This study census the entire population. The data was obtained through a questionnaire distributed to all employees as sample members. Next, the data obtained are tabulated and analyzed using multiple linear regression. Test the hypothesis using the IBM SPSS Software Version 26 assisted t-test and F-test. The results show that; Work discipline and work environment have a positive and significant effect on employee performance with a contribution of 94.6%. Meanwhile, partially work discipline and work environment have a positive and insignificant effect on employee performance. The better the discipline and work environment of employees, the better the performance of these employees. In other words, employee performance that can accelerate organizational goals can be realized if employee work discipline and the work environment can be optimized.